1990
DOI: 10.1159/000235217
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibodies Reactive with <i>Saccharomyces cerevisiae</i> in Inflammatory Bowel Disease: Is IgA Antibody a Marker for Crohn’s Disease?

Abstract: Sera from patients with Crohn’s disease (CD) and ulcerative colitis (UC) have been evaluated for antibodies reactive with Saccharomyces cerevisiae (anti-Sacc antibodies) using an enzyme-linked immunoassay (ELISA). IgG anti-Sacc antibodies were detected in 63% (25/40) of CD patients, compared with 15% (4/27) of UC patients (p <0.001) and 8% (5/60) healthy adult controls (p <0.001). Furthermore, the prevalence of detectable IgG anti-Sacc antibodies in adult patients with coeliac disease, dermatitis herpetiformis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 4 publications
2
38
0
Order By: Relevance
“…In a second publication, the same group confirmed their initial data and showed that the antibody response was specific for baker's yeast and did not include Candida albicans [8], By excluding yeast from the diet, these authors were also able to significantly reduce the Crohn's disease activity index in their patients [16]. Subsequently, the existence of ele vated antibody titers against baker's yeast in Crohn's dis ease has been supported by several publications from oth 41 er groups [9][10][11]. Lindberg et al [10] investigated 26 monozygotic twin pairs with inflammatory bowel disease and 52 healthy controls.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In a second publication, the same group confirmed their initial data and showed that the antibody response was specific for baker's yeast and did not include Candida albicans [8], By excluding yeast from the diet, these authors were also able to significantly reduce the Crohn's disease activity index in their patients [16]. Subsequently, the existence of ele vated antibody titers against baker's yeast in Crohn's dis ease has been supported by several publications from oth 41 er groups [9][10][11]. Lindberg et al [10] investigated 26 monozygotic twin pairs with inflammatory bowel disease and 52 healthy controls.…”
Section: Discussionmentioning
confidence: 71%
“…An elevated titer to a dietary compo nent like baker's yeast might have been considered an unspecific immune response that is unrelated to the pri mary mechanisms underlying Crohn's disease. Patients with Crohn's disease are known to have a leaky epithe lium which may lead to increased exposure of their immune system to foreign antigens [17], Serum anti bodies to cow's milk proteins have been claimed to be higher in Crohn's disease patients than controls [18,19], Lymphocyte proliferation may represent a more specific cellular immune response than elevated antibody titers, although the evidence accumulated by other groups sug gests that the elevated titers, particularly of IgA, represent a primary phenomenon rather than an epiphenomenon resulting from an impaired mucosal barrier [7][8][9][10][11], The results described in the present paper corroborate these previous findings. The similar baseline proliferation rate and the similar response to PHA among patients and con trols speak against a generally altered reactivity of lym phocytes in patients with Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASCA (IgA and IgG) are detected through their reactivity with sequences of mannose residues expressed in the cell wall mannan of Saccharomyces cerevisiae [21,25,26]. Saccharomyces cerevisiae is a "ubiquitous" yeast and occurs in diverse places naturally, on plants and in the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some of the familial studies have yielded conflicting data. For example, one group showed increased ASCA production in familial vs sporadic CD [7] , but others have shown equal or increased ASCA prevalence for sporadic CD [9,[16][17][18] . Thus, the case for an environmental etiology for ASCA has been articulated as well.…”
Section: Introductionmentioning
confidence: 99%